Repeat posterior fossa exploration and external neurolysis for recurrent trigeminal neuralgia following microvascular decompression - Liu, Zhong; Xu, Jiao; Ren, Ming-Liang; Xu, Min-Hui; Chen, Sha; He, Xu-Zhi; Wang, Xu-Hui (Frontiers in Surgery, 2026)
ObjectiveRecurrence of trigeminal neuralgia (TN) after microvascular decompression (MVD) poses a challenge for neurosurgeons. This study aimed to investigate the effect of repeat posterior fossa exploration (RPFE) and external neurolysis for TN recurrence following MVD.MethodsTotally, 38 TN patients who experienced recurrence after MVD were included. All patients underwent RPFE and limited neurolysis. The Barrow Neurological Institute Pain Intensity Scale were utilized to evaluate preoperative pain and postoperative outcomes.ResultsThe median follow-up period was 63.8 months (range: 5–112 months). Thirty-three out of the 38 patients achieved excellent outcomes, 4 had good outcomes, and 1 experienced failure. The rates of complete pain relief was 92% immediately post-surgery and 86.8% at the final follow-up. Re-exploration revealed Teflon adhesion in almost all patients (92%). Complications included new facial numbness (n = 5), temporary facial weakness (n = 3), hearing loss and tinnitus (n = 1), wound infection (n = 1), and postoperative hemorrhage (n = 1).ConclusionsTeflon adhesion was frequently observed upon re-exploration. A substantial majority of TN patients experiencing recurrence post-MVD achieved positive outcomes via RPFE and neurolysis. Complications, particularly facial numbness attributed to premature excessive Teflon dislodgement, continue to pose challenges. However, limited neurolysis, have proven effective in minimizing these complications.